Hasil Belajarku Luar Biasa dengan Menggunakan Mind Mapping dan Diiringi Musik Klasik - Hervina Elsafitri; Annisa Rahmi; Zuliana Wijaya; Tuti Rahmi Utari Febriani (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
The purpose of this research is to find out whether the learning method using mind mapping and listening to classical music can improve student learning outcomes. The research design is an experimental design. Specifically using the pretest-posttest Control Group Design. Based on the results of the calculation of the N-gain test, the experimental group's score was 90.44%, where this average category was effective in increasing the learning outcomes of class XI high school students. Based on the results of the calculation of the N-gain test, the control group's score was 57.42%, where this average category was effective enough to improve the learning outcomes of class XI high school students.